Effects of ultrasonic treatment on the structure and rehydration peculiarity of freeze-dried soy protein isolate gel. (April 2021) - Liang, Yaru; Teng, Fei; He, Mingyu; Jiang, Lianzhou; Yu, Jingwen; Wang, Xibo; Li, Yang; Wang, Zhongjiang
Graphical abstract: Highlights: The structure of freeze-dried SPI gel was affected by ultrasonic treatment. The storage modulus of freeze-dried SPI gel was affected by ultrasonic treatment. Ultrasonic treatment affects network structures of freeze-dried SPI gel. Ultrasonic treatment affects the rehydration peculiarity of freeze-dried SPI gel. Abstract: Different levels of ultrasonic power (0, 100, 200, 300, 400, and 500 W) were applied to soybean protein isolate [SPI] solution to evaluate the effects of ultrasonic treatment (4°C) on the microstructure and rehydration peculiarity (rehydration kinetics, texture profile analysis [TPA], water-holding capacity, and water distribution) of freeze-dried SPI gel. Suitable ultrasonic treatment (4°C) reduced the average size and increased the energy storage modulus of SPI solution relative to those of untreated SPI solution. The formed gel has a uniform and dense network structure. The improved the water-holding capacity and texture, and enhanced the capillary percolation of freeze-dried SPI gel during rehydration. And enlarged the size of holes in rehydrated SPI gel and made the water release rate, relaxation time T22, M22, gel hardness of rehydrated SPI gel were significantly higher than that of fresh SPI gel ( P < 0.05). Therefore, freeze-dried SPI gel with a fine texture and high rehydration rate can be prepared when ultrasonic power of 300 W.